2017
DOI: 10.1007/s00226-017-0936-3
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and mechanical properties of various species of Madagascan woods

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Any correspondence concerning this service should be sent to the repository administrator: staff-oatao@listes-diff.inp-toulouse.fr Abstract The low-temperature molecular mobility of three different wood species was analyzed, with the two major constituents-cellulose and lignin-as reference. Mechanical and dielectric dynamic techniques were used. In order to observe the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…With this understanding, the DS results clearly illustrate the impact of the chemical composition of the paper analyte on the dielectric loss response, and are consistent with investigations of wood species and cotton using other dielectric spectroscopy techniques [3]. The results suggest that resonant cavity DS could be a useful tool for discriminating between paper of different compositions.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…With this understanding, the DS results clearly illustrate the impact of the chemical composition of the paper analyte on the dielectric loss response, and are consistent with investigations of wood species and cotton using other dielectric spectroscopy techniques [3]. The results suggest that resonant cavity DS could be a useful tool for discriminating between paper of different compositions.…”
Section: Resultssupporting
confidence: 82%
“…Dielectric spectroscopy (DS) probes the relaxation dynamics of dipoles and mobile charge carriers in response to an alternating electric field and provides information on the molecular fluctuations of dipoles within a matrix in response to rapidly changing electromagnetic fields [3]. This molecular polarization involves rotational reorientation in rapidly changing electromagnetic fields, making DS particularly well suited to examine the dynamics of molecules in confined spaces, such as in paper products.…”
mentioning
confidence: 99%
“…It is also possible that lignin has secondary relaxation peaks, which could occur within the studied temperature range. This has been proposed based on dielectric analysis and thermostimulated current analysis (TSC), with a β peak for lignin occurring near -70°C in the experiments of Roig et al (2017). By contrast they located γ for cellulose at a lower temperature (circa -135°C), and commented that this frequently dominates the lignin β peak.…”
Section: Discussionmentioning
confidence: 99%
“…This was ascribed primarily to the effect of water on lignin, but also water on hemicellulose. Dielectric and DMA analysis by Roig et al (2017) indicated differences between three hardwood timbers, which were attributed to the molecular mobility, due to the modifying effect of the specific environment within woods of differing macromolecular arrangement.…”
Section: Discussionmentioning
confidence: 99%
“…If the sample is not mutilated or destroyed during analysis using one of these techniques, then direct contact with the substrate is required, which may result in damage or contamination of the analyte (Blumich et al 2003). It is well established that paper and pulp materials, like other biomaterials, have characteristic dielectric profiles which can be used to identify and differentiate between specimens (Joshi et al 2015;Roig et al 2017).…”
Section: Introductionmentioning
confidence: 99%